Evaluation of Salivary Alkaline Phosphatase and Albumin in HIV Infected Patients: A Historical Cohort Study - Ahmadi-Motamayel, Fatemeh; Vaziri-Amjad, Samaneh; Davoodi, Poorandokht; Goodarzi, Mohammad T.; Poorolajal, Jalal (Infectious Disorders - Drug Targets, 2019)
Background: Saliva is a very important complex biological oral fluid .Antioxidants are present in all body fluids. Uric acid, albumin and vitamins are some of the non- enzymatic molecular antioxidants. Alkaline phosphatase is related to cell injury and death. Objectives: The aim of this study was the evaluation of salivary alkaline phosphatase and albumin level in HIV positive patients in comparison to healthy control group. Methods: Case groups were 49 HIV positive subjects, compared with 49 healthy control group. Oral clinical examination was carried out. Five ml unstimulated whole saliva was collected during 5 min with the Navazesh method. Alkaline phosphatase was determined by spectrophotometric assay. Albumin was assessed by the nephelometric method. Results: The results of this study showed significantly lower salivary albumin in the case group in comparison to healthy control group (p= 0.001). HIV positive group had greater alkaline phosphatase than the healthy control group. However, this difference was not statistically significant (p=0.458). Conclusion: Salivary albumin level was significantly decreased and salivary alkaline phosphatase level slightly increased in HIV positive patients in comparison to healthy control group. All of the HIV infected patients were in early phase of HIV infection with normal immune status. More research is needed to estimate these enzymes changes in late phase of HIV infection and AIDS step.
Keywords: Alkaline phosphatase